Peri-Implantitis Prevention: A Multi-Level Evidence-Based Approach from Primordial to Quaternary Prevention - Ahmed, Anam; Mannan, Huda; Tamij, Nusrat (Journal of Dentistry and Allied Science, 2025)
Peri-implantitis is an inflammatory disease around soft and hard tissues of the dental implants, and is one of the most common diseases that leads to cases of failure of the dental implant therapy in the long term. The rising prevalence of peri-implant diseases highlights the critical need for prevention protocols, characterized by progressive bone loss and possible loss in implant function. Moreover, it requires a thorough, multi-dimensional preventative approach to preserve patient oral health and overall wellness. This review aims to assess the existing evidence-based prevention strategies for Peri-implantitis, including primordial, primary, secondary, tertiary, and quaternary prevention levels Journal of Dentistry and Allied Science, Vol. 8 No 1: 47-52